EFEKTIVITAS PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMPUTER TERHADAP SIKAP MAHASISWA PADA PERKULIAHAN GEOMETRI RUANG (Universitas PGRI Sumatera Barat, 2014)
The background of this research is the use of unvaried learning resources causes tired and bored students in following the lecture. Boredom experienced make the students difficult to think creatively, so that they only work based on the example problems and discussion of the lecturer given. To solve the problems, one of the media that can be used is a computer-based learning media. This research aims to see the effectiveness of student learning media towards the attitudes of students in the subject of Space Geometry. Type of research is a developmental research. This research developed a computer-based learning media on the subject of space geometry. Model of development used on this research is a model of instructional Development Institute (IDI). IDI applies the principles of systems approach. There are three stages of a systems approach, namely the discovery (define) or a needs analysis, development (develop), and evaluation (Evaluate). The instrument used in this research was a questionnaire of attitude. Computer-based instructional media on the lecture of Space Geometry has a positive attitude towards students. It is found from the results of the questionnaire that student attitudes toward computer-based learning media are interested and very interested in computer-based learning media. This is pictured out by the results of percentage ranging between 66% - 89%. Based on the previous explanation, it can be concluded that the use of computer-based learning media has a positive influence, so that it can be used as a medium of learning in the subject of Space Geometry.